The Neuropsychiatric Terminology in the sixteenth century Quechua - Cabieses Molina, Fernando (1963)
Research on our pre-Columbian cultures have been highly concentrated in waste materials on archeology gives us. When looking for the origins and realities of this point, it is easy to fall into the temptation to turn our attention to the human remains, pottery, tools, clothing, and the ruins of cities and temples. This leads to the situation to know what the man went and did; but without knowing what he thought. These lines are an attempt to follow the light path we traced the History Institute of the Arts Faculty of our University, to put within easy reach of scholars vocabularies Fray Domingo de Santo Tomás (6) and Diego González Holguin (1), showing us the Quechua of the late sixteenth century.